Pengaruh Intervensi Model Pemberdayaan Keluarga Terhadap Pengetahuan, Praktik Perawatan Diri, dan Motivasi Berobat pada Dewasa Hipertensi Di Masyarakat - Abidin, La Syam; Kainama, Norce (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2025)
Hypertension is a global health problem with an increasing prevalence and low treatment adherence. This study aimed to assess the effectiveness of the Family-Centered Empowerment Model (FCEM) in improving knowledge, self-care practices, and treatment motivation among adults with hypertension. A pre-experimental one-group pretest-posttest design was employed, involving 38 hypertensive participants selected through purposive sampling in the working area of Letwaru Primary Health Center, Central Maluku Regency. The FCEM intervention consisted of six sessions lasting 60–90 minutes each. Data were collected using structured questionnaires before and three months after the intervention and analyzed using descriptive statistics and the Wilcoxon test. The results indicated substantial enhancements in knowledge, self-care practices, and treatment motivation post-intervention (p < 0.05). The findings indicate that FCEM effectively empowers patients and families, enhances understanding of hypertension, strengthens self-care behaviors, and increases adherence motivation. FCEM has the potential to be implemented as a family-based intervention approach in primary healthcare to support sustainable hypertension management.